2012
DOI: 10.1016/j.semnephrol.2012.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Treatment That Target Protective Mechanisms Against Diabetic Nephropathy

Abstract: Summary Diabetes results in vascular changes and dysfunction, and vascular complications are the leading cause of morbidity and mortality in diabetic patients. There has been a continual increase in the number of diabetic nephropathy patients and epidemic increases in the number of patients progressing to end-stage renal diseases. To identify targets for therapeutic intervention, most studies have focused on understanding how abnormal levels of glucose metabolites cause diabetic nephropathy, which is of paramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 66 publications
0
20
1
1
Order By: Relevance
“…These deleterious effects may include but are not limited to proteinuria, hypertension, and thrombotic microangiopathy [248, 249]. For instance, cancer patients treated with bevacizumab, a humanized monoclonal antibody against VEGF, experienced aggravated pathological events including proteinuria, hypertension, extensive foot process effacement, and thrombotic microangiopathy [250]. Administration of anti-VEGF agent, mutation, or gene deletion of podocyte-specific VEGF in murine models also exhibited similar adverse consequences.…”
Section: Progression Of Renal Injury Through Diverse Signaling Patmentioning
confidence: 99%
See 1 more Smart Citation
“…These deleterious effects may include but are not limited to proteinuria, hypertension, and thrombotic microangiopathy [248, 249]. For instance, cancer patients treated with bevacizumab, a humanized monoclonal antibody against VEGF, experienced aggravated pathological events including proteinuria, hypertension, extensive foot process effacement, and thrombotic microangiopathy [250]. Administration of anti-VEGF agent, mutation, or gene deletion of podocyte-specific VEGF in murine models also exhibited similar adverse consequences.…”
Section: Progression Of Renal Injury Through Diverse Signaling Patmentioning
confidence: 99%
“…Administration of anti-VEGF agent, mutation, or gene deletion of podocyte-specific VEGF in murine models also exhibited similar adverse consequences. In addition, some studies have shown a beneficial role of VEGF which includes the prevention of progressive capillary rarefaction, promotion of capillary repair, improvement of renal injury, and prevention of functional and histologic abnormalities in diabetic nephropathy [250, 251]. In support of this evidence, Oltean et al's [251] transgenic podocyte-specific overexpression of VEGF-A165b in streptozotocin-induced diabetic mice demonstrated less glomerular hypertrophy, less mesangial expansion, and less GBM thickening.…”
Section: Progression Of Renal Injury Through Diverse Signaling Patmentioning
confidence: 99%
“…One approach is to identify novel drug targets by gaining a better understanding of the pathogenesis of diabetic nephropathy at the molecular level, as discussed by other articles in this issue 57 . However, going from the identification of a drug target to the development of a clinically effective intervention is a long and costly process and only a small number of compounds that enter the development pipeline end up being approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…По аналогии с опухолевым ростом, можно предположить, что в условиях дефицита супрессоров ангиогенеза (на ранних этапах ДН) в качестве антиангиогенной терапии была бы эффективна стратегия, направленная на ингибирование ростовых факторов, включая VEGF, и/или их рецепторов (FLK-1, FLT-1 и Tie2) [111,112]. Действительно, использование нейтрализующих VEGF специфических антител эффективно снижало степень гиперфильтрации, альбуминурии и гломерулярной гипертрофии почек у грызунов с экспериментальным диабетом [113].…”
Section: тихомиров и дрunclassified